Regional cerebral blood flow by SPECT imaging in Sturge-Weber disease: an aid for diagnosis. Issue 12 (December 1989) - Chiron, C; Raynaud, C; Tzourio, N; Diebler, C; Dulac, O; Zilbovicius, M; Syrota, A
Abstract : Regional cerebral blood flow (rCBF) was studied using SPECT (single photon emission computed tomography) with 133-Xenon in 13 patients with confirmed Sturge-Weber disease, aged 9 months to 18 years. CT scan, performed at the same time, showed evident cerebral angioma in 10 but not in three. A marked hypoperfused area was found in all patients, ranging from -32% to -72% and of the same location as the CT signs. The hypoperfusion seems to result from post ictal phenomenon as well as from chronic ischaemia. SPECT imaging is therefore a sensitive method for visualising intracranial angioma in Sturge-Weber disease and it provides an aid for diagnosis when a CT scan is not reliable.